FAKTORI RIZIKA ZA PRODUZENU HOSPITALIZACIJU KOD COVID 19 PACIJENATA - Zivkovic Zaric, Radica S (PONS - medicinski časopis, 2022)
Background/Objective: Although some factors that may influence hospitalization of COVID 19 patients are already known (hypocalcemia and hyponatremia, bilateral pneumonia), there is a number of other potential predictors that were not investigated previously.The aim of our study was to investigate further potential predictors of the length of hospitalization among patients with COVID 19. Methods: The study was designed as observational, retrospective cohort investigation of factors associated with length of stay in a tertiary care hospital of patients admitted primarily due to COVID 19. Main outcome of the study was length of hospitalization. Secondary outcomes were mortality rate, rate of Acute Respiratory Distress Syndrome (ARDS) and rate of severe sepsis. Results: There were 110 patients whose primary reason for admission was COVID 19. The average age of our study sample was 56 years and the male gender was predominant. The median length of hospitalization was 12 days, and most of the patients lived in a city. Our study suggested that Charlson comorbidity index, antipsychotics, beta-blockers, metronidazole and oxygen inhalation therapy could prolong stay of COVID 19 patients in a hospital. On the other hand, corticosteroid therapy, blood transfusion, parenteral proton pump inhibitors, and macrolides reduced the length of hospitalization. Conclusions: Co-morbidities and prescribing drugs that are used for treatment of delirium or post-antibiotic diarrhea are associated with prolonged hospitalization of COVID 19 patients, while medication used for treatment of complications may shorten stay in a hospital and probably improve survival.